PRKX down-regulates TAK1/IRF7 signaling in the antiviral innate immunity of black carp Mylopharyngodon piceus - Yang, Xiao; Ai, Yue; Chen, Liang; Wang, Chanyuan; Liu, Ji; Zhang, Jie; Li, Jun; Wu, Hui; Xiao, Jun; Chang, Mingxian; Feng, Hao (Frontiers in Immunology, 2023)
TGF-β-activated kinase-1 (TAK1), tightly related to innate immunity, is phosphorylated and activated by X-linked protein kinase (PRKX) in humans and mammals, which belongs to the c-AMP-dependent protein kinase family. However, the relationship between PRKX and TAK1 remains unknown in teleost. It has been reported in vertebrates for the first time that TAK1 of black carp (bcTAK1) interacts with bcIRF7 and is capable to up-regulate bcIRF7-mediated IFN signaling in our previous study. In this study, the role of PRKX homologue of black carp (Mylopharyngodon piceus) (bcPRKX) in bcTAK1/IFN signaling has been explored. Overexpression of bcPRKX suppressed the transcription of interferon promoters but enhanced the transcription of NF-κB promoter. Mylopharyngodon piceus kidney (MPK) cells transfected with shRNA targeting bcPRKX gene presented enhanced antiviral activity against spring viremia of carp virus (SVCV), in which the mRNA levels of the antiviral proteins were increased, including MX1, Viperin and PKR. Overexpressed bcPRKX dampened bcTAK1/bcIRF7/IFN signaling in the luciferase reporter assay and plaque assay. The interaction between bcTAK1 and bcPRKX has been identified by the immunofluorescence (IF) staining and co-immunoprecipitation (co-IP) assay. In addition, we found that bcPRKX can trigger the degradation of bcTAK1. However, the lysosome inhibitor chloroquine, but not the proteasome inhibitor MG-132, prevented the bcTAK1 degradation mediated by bcPRKX. Thus, we conclude that bcPRKX inhibits bcTAK1/bcIRF7/IFN signaling during the innate immune activation by targeting bcTAK1 and triggers lysosome-dependent degradation of bcTAK1.